2015
DOI: 10.1093/humupd/dmv024
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary defined role of the mitochondrial DNA in fertility, disease and ageing

Abstract: Understanding the forces and processes that underlie mtDNA evolution among different species increases our knowledge on the detrimental consequences that individuals can have from these evolutionary end-points. Alternative outcomes in animals, fungi and plants will lead to a better understanding of the inheritance of mtDNA disorders and mtDNA-related fertility problems. These will allow the development of options to ameliorate, cure and/or prevent mtDNA diseases and mtDNA-related fertility problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 215 publications
0
50
0
Order By: Relevance
“…This is close to the frequency of 18.9% we report here for zebrafish. This is further corroborated by a similar degree of variation in mtDNA copy number in human oocytes (Otten and Smeets 2015), which suggests variation in the mtDNA bottleneck size and subsequent differences in the de novo risk. In humans, it has been estimated that about 5% of the mutations in the mtDNA alter a conserved nt and are thus potentially pathogenic (Jacobs et al 2007).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is close to the frequency of 18.9% we report here for zebrafish. This is further corroborated by a similar degree of variation in mtDNA copy number in human oocytes (Otten and Smeets 2015), which suggests variation in the mtDNA bottleneck size and subsequent differences in the de novo risk. In humans, it has been estimated that about 5% of the mutations in the mtDNA alter a conserved nt and are thus potentially pathogenic (Jacobs et al 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Most likely in humans, these pathogenic mutations are filtered out by mitophagy (Song et al 2014) or are at high levels not compatible with embryonic survival and remain unnoticed at low levels. Given the high sequence homology (72%; NCBI blast performed) between the mtDNA genome of zebrafish and humans and the high evolutionary conservation of the mtDNA bottleneck in animal species (Wolff et al 2011;Guo et al 2013;Otten and Smeets 2015;Otten et al 2016), our results indicate that the de novo risk might be similar among zebrafish and humans. Indeed, a study in 26 human oocytes (Jacobs et al 2007), seven oocytes (26.9%) were found to harbor de novo variants.…”
Section: Discussionmentioning
confidence: 84%
“…The number of mitochondria in each cell type reflects its energy demand; tissues such as muscle and brain have large numbers of mitochondria due to their high energy requirements. The number of mitochondria, estimated by mtDNA copy number, can also vary with the developmental stage 2,3 : human and mouse fertilizable oocytes have around 250,000 copies of mtDNA, each cell of a blastocyst (late-stage preimplantation embryo) has about 1,000, and there may be many fewer, from 10-200 per cell, during early development of the embryo after implantation, at the time the primordial germ cells are specified. Interestingly, direct measurements of mtDNA copy numbers in isolated mouse primordial germ cells suggest that their number may be higher (>200) than those of somatic cells at the same developmental stage 4 .…”
mentioning
confidence: 99%
“…Oxidative stress also increases permeability in mitochondria (60), which exposes mitochondrial DNA to damaging elements (61). Damaged mitochondrial DNA has been linked to reproductive aging (55, 62). Mice lacking the glutamate cysteine ligase modifier subunit, the rate-limiting enzyme in production of the most abundant intracellular antioxidant, glutathione, showed increased oxidative stress, apoptosis in follicles, and accelerated age-related decline in primordial follicles compared to wild type mice (63).…”
Section: Menopausementioning
confidence: 99%
“…Consumers have no way of knowing if the ingredients in their cosmetics are 1,4-dioxane free, and the Organic Consumers Association commissioned a study in 2008 that found 1,4-dioxane in a significant percentage of the organic products analyzed (61). 1,4-dioxane has been shown to be carcinogenic in animals (62). …”
Section: Figurementioning
confidence: 99%